2011
DOI: 10.1124/jpet.111.180992
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Stimulates Angiogenesis and Increases Hypoxia-Inducible Factor-1α Accumulation via Phosphatidylinositol 3-Kinase/Akt Pathway

Abstract: Astragaloside IV is the major active constituent of Astragalus membranaceus, which has been widely used for the treatment of cardiovascular diseases in China. The aim of this study was to determine the angiogenic effect of astragaloside IV and its underlying mechanism. We used the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay, Western blotting, real-time polymerase chain reaction, and immunofluorescence to detect the effect of astragaloside IV on proliferation of human umbilical vein endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…These results suggest that increasing the activation of the JNK and p38 MAPK pathways might play a prominent role in renal tubular cell apoptosis (thus, subsequently accelerating the progression of renal tubulointerstitial fibrosis), and the inhibitory effect of AS-IV on cell apoptosis may be related to the inhibition of these two MAPK signaling pathways. Similar studies have been performed on the protective effect of AS-IV in renal injury and pathology (Meng et al, 2011;Zhang et al, 2011;Li et al, 2012;Qin et al, 2012;Gui et al, 2013;Qi et al, 2014). Meng et al (2011) performed a study in UUO rats using AS-IV and ferulic acid as treatments.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that increasing the activation of the JNK and p38 MAPK pathways might play a prominent role in renal tubular cell apoptosis (thus, subsequently accelerating the progression of renal tubulointerstitial fibrosis), and the inhibitory effect of AS-IV on cell apoptosis may be related to the inhibition of these two MAPK signaling pathways. Similar studies have been performed on the protective effect of AS-IV in renal injury and pathology (Meng et al, 2011;Zhang et al, 2011;Li et al, 2012;Qin et al, 2012;Gui et al, 2013;Qi et al, 2014). Meng et al (2011) performed a study in UUO rats using AS-IV and ferulic acid as treatments.…”
Section: Discussionmentioning
confidence: 97%
“…Akt is activated in response to PI3K and its lipid products phosphatidylinositol 3, 4, 5-trisphosphate (Ptdlns [3,4,5]P3, PIP 3 ) and Ptdlns(3,4) P 2 (PIP 2 ) [40]. Activated PI3K/Akt signaling induces further eNOS activation which is localized on the cellular membranes and leads to the production of NO [41]. eNOS is the NOS isoform that is expressed abundantly in the cardiovascular tissues, especially in the endothelium.…”
Section: The Effects Of Agiv On the Pi3k/akt/enos Signaling Pathwaymentioning
confidence: 99%
“…The activation of the PI3K/Akt pathway caused by AGIV is a pivotal event in suppressing cardiomyocyte apoptosis [53]. AGIV Color version available online treatment significantly stimulates angiogenesis via the PI3K/Akt signaling pathway [41]. As a Ca 2+ antagonist, AGIV blocks the superior receptor-operated Ca 2+ and relaxes the vessels by regulating NO from vascular endothelial cells and vascular smooth-muscle cells [54].…”
Section: The Importance Of Agivmentioning
confidence: 99%
“…It may induce a keratinocyte proliferation and migration, which is an essential feature of reepithelialization [12]. It also promotes vascular cell migration and proliferation, which is an important component of new vessel formation and vascular maturation [35]. In the current study, we found that local administration of AS-IV into cutaneous wounds was sufficient to facilitate the rate of wound healing in diabetic mice.…”
Section: Discussionmentioning
confidence: 88%